Antiepileptic Drug Monitoring - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The appropriateness of antiepileptic drug (AED) level monitoring was assessed in a tertiary care center performing more than 10,000 AED level determinations per year and reported from the Brigham and Women's Hospital, Boston, MA.